Diagnosis of Intercrops in Poplar Based Agroforestry - Dhiman, R. C. (Indian Forester, 2012)
Results of a survey conducted during the harvesting of block plantations to diagnose the intercrops grown in poplar based agroforestry (PBAF) are presented here. Informations were collected from 220 sampled plantations from 172 villages, 69 tehsils, 28 districts in 4 states viz, Punjab, Haryana, Uttar Pradesh and Uttrakhand. Wheat was found as main crop grown in 51.67% cases followed by sugarcane, fodder(shorghum/berseem)), maize, jawar/bajra, paddy, dhencha (green manure) and others. The intensity of cropping was more in winter (rabi) season than in summer (kharif) season. Farmers stopped growing intercrops much earlier in summer season than in winter season. Survey further identified intercrops grown in different locations from first year to harvesting age. Validation of the results with the information collected on intercrops in PBAF through field staff of Wimco Ltd was largely in consonance with the findings of the survey. The survey also estimated planting of 24.34 million poplar saplings throughout the region of intensive poplar culture (RIPC) during 2009-10 planting season, out of which 58.38% were in compact blocks and 41.62% were as boundary plantations.